Continuity-Based Environmental Communication: Ecological Persistence in Observational Documentary - Fajaria Menur Widowati; Sri Widayati; Feriz Rizki Aditya (Jogjakarta Communication Conference (JCC), 2026)
Environmental communication has traditionally emphasized crisis framing, advocacy narratives, and audience impact, positioning documentary film as a persuasive instrument. Recent relational perspectives, however, suggest that ecological meaning may also emerge through everyday practice rather than explicit rhetorical confrontation. This study examines how an observational documentary can function as environmental communication through the articulation of routine ecological practices. Using a qualitative interpretative approach, the study conducts close textual analysis of the 24-minute documentary Pusenai – The Last Dayak Basap (2018), focusing on recurring practices, scene sequencing, editing structure, and visual contrast. The findings show that environmental meaning is constructed through the sustained representation of everyday activities, including rattan weaving, forest foraging, communal interaction, and cultural transmission. These practices are mediated through repetition, duration, and continuity, allowing ecological relations to emerge as lived and ongoing conditions rather than as crisis-driven narratives. The study proposes ecological persistence as an analytical concept describing the continuity of human–nature relations as structured within observational documentary form. This perspective extends environmental communication beyond persuasion-centered paradigms by highlighting continuity-based representation as a significant mode of ecological articulation. The findings also suggest that environmental communication may operate through perceptual visibility rather than explicit persuasion.